2006
DOI: 10.1073/pnas.0603529103
|View full text |Cite
|
Sign up to set email alerts
|

Differences in vertebrate microRNA expression

Abstract: MicroRNAs (miRNAs) attenuate gene expression by means of translational inhibition and mRNA degradation. They are abundant, highly conserved, and predicted to regulate a large number of transcripts. Several hundred miRNA classes are known, and many are associated with cell proliferation and differentiation. Many exhibit tissue-specific expression, which aids in evaluating their functions, and it has been assumed that their high level of sequence conservation implies a high level of expression conservation. A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
185
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 35 publications
11
185
1
3
Order By: Relevance
“…Skeletal precursors across vertebrate species express mirn140 [21][22][23][24] and mirn140 occupies the orthologous intron in wwp2 of zebrafish, human, and other vertebrates ( Supplementary Fig. 1), prompting the hypothesis that Mirn140 plays a conserved role in skeletogenesis across vertebrate species.…”
Section: Mirn140 and Pdgf Signaling Regulate Palatal Development In Zmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal precursors across vertebrate species express mirn140 [21][22][23][24] and mirn140 occupies the orthologous intron in wwp2 of zebrafish, human, and other vertebrates ( Supplementary Fig. 1), prompting the hypothesis that Mirn140 plays a conserved role in skeletogenesis across vertebrate species.…”
Section: Mirn140 and Pdgf Signaling Regulate Palatal Development In Zmentioning
confidence: 99%
“…Most Pdgfc mutants have cleft palate 15 MicroRNAs (miRNAs) provide a unique mechanism for modulating signaling pathways [17][18][19][20] . Skeletogenic, including palatal, precursors express mirn140 (miR-140) in teleosts 21 and amniotes [22][23][24] , suggesting that Mirn140 may modulate signaling during palatogenesis across vertebrate species. Despite the function of miRNAs in development and the importance of neural crest in evolution and disease, no miRNA has yet been shown to regulate neural crest development or cellular behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have shown that miRNA expression during development is highly tissue-specific (9)(10)(11)(12), which suggests that miRNA may be involved in specifying and maintaining tissue identity. For example, the expression of miR-124a is restricted to the brain and spinal cord in the fish and the mouse, and to the ventral nerve cord in the fly (13).…”
mentioning
confidence: 99%
“…Plasterk and colleagues have used an ISH method based on Locked Nucleic Acid (LNA) oligonucleotide probes to detect mature miRNAs in whole mounts of zebrafish and mouse embryos [ 11,12 ]. The LNAbased ISH methodology has been applied to whole-mount embryos from a variety of vertebrate species, including chicken and medaka [ 13,14 ], and for the analysis of adult human brain sections [ 15 ] as well as mouse tissue sections [ 16,17 ]. Independently, we have developed a miRNA ISH method based upon RNA oligonucleotide probes and have used this method for the detection of mature miRNAs in tissue sections from embryonic and adult mice [ 18 ], as well as from rat and human brains (this article) and zebrafish (our unpublished observations).…”
Section: Introductionmentioning
confidence: 99%